Effects of marble waste on shear strength and pullout resistance of sand reinforced with Glass Fiber-Reinforced Polymer (GFRP) bars - Shabir Hussain; Irshad Ahmad; Fasih Ahmed Khan; Waqas Ahmad; Beenish Jehan Khan (Case Studies in Construction Materials)
The growing emphasis on sustainability and environmental concerns is prompting researchers to explore ways to utilize waste materials. One such material is Marble Waste (MW), produced in large quantities during the production, cutting, and dressing of marble stones. The disposal of MW poses waste management and environmental challenges. In this study, MW, including Marble Powder (MP) and Marble Rubble (MR), were used as partial replacements for sand in GFRP-reinforced granular soil. The methodology involved determining basic geotechnical properties and Optimum Mixing Ratios (OMRs) for MW-sand (MWS) mixtures. A large shear box apparatus (0.6 m x 0.6 m x 0.3 m) was used to evaluate the shear strength of sand and optimum MWS samples, as well as the pullout resistance of 8 mm, 12 mm, 16 mm, 20 mm, and 25 mm Thread-Wrapped (TW) GFRP bars embedded in both sand and MWS samples. Sand with 14 % MP, 28 % MR, and 21 % (MP+MR) by weight were identified as OMRs. The optimum addition of MW to sand significantly improved both shear strength and pullout resistance of GFRP-reinforced sand. For instance, sand with the optimum addition of MP, MR, and MP+MR showed improvements of 8.2 %, 15 %, 23.4 %, 15.9 %, 21.2 %, and 24.5 % in the peak and ultimate angles of internal friction, respectively. Additionally, the peak pullout resistance of a 12 mm TW-GFRP bar embedded in the optimum MWS samples increased by 105 %, 126 %, and 139 %, compared to the bar embedded in the pure sand sample. Therefore, GFRP bars embedded in optimized MWS mixtures are proposed as a sustainable and eco-friendly soil-reinforcement method, which is also helpful in reducing the depletion of natural resources and promoting a circular economy.